Profile of Female Victims of Alleged Sexual Assault Cases Reported to Dr.B.R. Ambedkar Medical College, Bengaluru - Karthik SK; Mohana Velu J; Jayaprakash G (Institute of Medico-legal Publications Pvt Ltd, 2021)
Sexual violence is one of the most heinous crimes against women. Sexual assault is a violation of the dignityof a person. The present prospective descriptive study was conducted in the department of Forensic Medicine,Dr.B.R.Ambedkar medical college, Bengaluru, Karnataka, South India for a period of one year from Januaryto December 2014, where victims of alleged sexual assault cases were brought in for examination. Majorityof victims, 77 out of 149 were between 16 - 20 years. 107 victims (71.8%) were educated up to school level.101 victims were students. 85.2% cases were unmarried victims. In 106 (71.1%) cases, accused was knownto the victim. 54 cases (36.3%) of sexual assault occurred in the house of the victim or accused. 65.1%victims in our study had bodily injuries.